Motivational Factors and Organizational Commitment Factors Affecting Employee Work Performance in a Shopping Center Business in Bangkok - Thongware, Benyanee; Siriwongse, Tongfu (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this independent research were 1) Examine the level of employee motivation in a shopping center business in Bangkok. 2) Assess the level of organizational commitment among employees in a shopping center business in Bangkok. 3) Evaluate the level of work performance of employees in a shopping center business in Bangkok. 4) Analyze employee work performance based on individual factors in a shopping center business in Bangkok. 5)Investigate the impact of motivational factors and organizational commitment factors on employee work performance in a shopping center business in Bangkok. The sample group for this study consists of 200 employees working in the back-office departments of a shopping center business in Bangkok. Data analysis is conducted using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as multiple regression analysis to examine relationships between variables. The results of the study revealed that employees in a shopping center business in Bangkok with different educational backgrounds exhibited significant differences in work performance at the 0.05 significance level. Furthermore, motivational factors and organizational commitment factors influenced employee work performance. Specifically, normative commitment, continuance commitment, job achievement, and recognition had a positive impact on work performance. Among these factors, normative commitment had the greatest effect on employee work performance, followed by job achievement, continuance commitment, and recognition, respectively.